The Impact of Political Institutionalization Issues Within the United Development Party (PPP) Following the Change of the General Chairperson in 2022 on Internal Solidarity in the 2022 Simultaneous Selections - Tegar Putra Munggaran; Meidi Kosandi (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
This research want to investigates the impact of political institutionalization issues, specifically the contentious leadership change in 2022 (from Suharso Monoarfa to Mardiono), on the internal solidarity of the United Development Party (Partai Persatuan Pembangunan/PPP) leading up to the 2024 General Election in Indonesia. Political parties are critical pillars in a democratic system, and their institutional strength determines their effectiveness. However, PPP’s history is marred by recurring internal conflicts that challenge its institutional stability. This research employs a qualitative approach with a case study design, collecting data through in-depth interviews with key party elites, regional functionaries, and document analysis. The findings reveal that the abrupt and controversial replacement of the Chairman severely undermined internal solidarity, manifesting as deep divisions, erosion of trust, and fragmented support at the grass roots. These internal institutional problems directly contributed to PPP's failure to meet the parliamentary threshold in the 2024 election. The study concludes that neglecting robust institutionalization processes, particularly during leadership transitions, severely compromises a party's electoral viability and long-term stability